Implementasi Pembelajaran Berbasis Proyek dalam Mata Pelajaran Bahasa Indonesia Pada Anak Kelas V di MIN 01 Kota Bengkulu - Aldila, Delvita Jesika; Adisel, Adisel; Gilang, M. Ilham (MUDABBIR Journal Research and Education Studies, 2025)
This study aims to describe the implementation of the Project-Based Learning (PjBL) model in teaching the Indonesian language to fifth-grade students at MIN 01 Bengkulu City and its impact on students’ motivation and language skills. The study employed a qualitative descriptive approach, collecting data through observation, interviews, and documentation. The findings reveal that PjBL implementation consists of three main stages: planning, implementation, and evaluation. During the planning stage, teachers designed contextually relevant projects such as creating classroom wall magazines and writing activity reports. In the implementation phase, students actively participated in group collaboration, information exploration, and project development, while teachers acted as facilitators. Evaluation was conducted comprehensively, covering process, product, and students’ collaborative behavior. The results indicate that PjBL effectively enhanced students’ writing, speaking, critical thinking, and sense of responsibility and teamwork. Despite challenges such as time constraints and limited resources, teachers managed them through innovative classroom strategies. Overall, the PjBL model proved effective in creating contextual, creative, and student-centered learning experiences in Indonesian language instruction.